How do you simplify #(-2h^5 - 10h^2 )/(8h^6)#?

2 Answers
Apr 26, 2017

Answer:

#=-1/4h-5/(4h^4)#

Explanation:

  1. Separate the equation
    #(-2h^5)/(8h^6)-(10h^2)/(8h^6)#

  2. Separate numbers from variables
    #-2/8(h^5)/h^6 -10/8(h^2)/h^6#

  3. Divide. Remember to minus the indices from each other when dividing
    #-1/4h^(5-6)-5/4h^(2-6#

  4. Simplify
    #-1/4h^1-5/4h^-4#
    #=-1/4h-5/(4h^4)#

Apr 26, 2017

Answer:

#((-h^3-5))/(4h^4)#

Explanation:

#(-2h^5-10h^2)/(8h^6)#

#:.=(2h^2(-h^3-5))/(8h^6)#

#:.=((-h^3-5))/(4h^(6-2))#

#:.=((-h^3-5))/(4h^4)#